Структурно-функціональна модель вальниць опорних вузлів рейкового транспорту - Гайдамака, Анатолій Володимирович; Клітной, Володимир Вікторович; Клітной, Віктор Володимирович (Національний технічний університет "Харківський політехнічний інститут", 2025)
Тип роликових вальниць букс (опорних вузлів) рейкового транспорту (РВБРТ) залежить від умов експлуатації в тій чи іншій державі. У Великобританії, США, Японії, Польщі залізничні вагони оборудують колісними парами з дворядними конічними роликовими вальницями. Для вагонів Австрії, Германії, України застосовують вузли з двома циліндричними роликовими вальницями, а для Швеції типовим є буксовий вузол з двома сферичними роликовими вальницями. Базовою конструкцію для структурно-функціональною аналізу вибрано найбільш масові серійні циліндричні РВБРТ, що застосовують в українських вантажних і пасажирських вагонах (майже 99 % від загальної кількості). Виконано структурну декомпозицію базових вузлів вальниць, відповідно до функцій призначення. За побудованою структурно-функціональною моделлю циліндричної вальниці, виявлено функціональні взаємозв’язки між елементами її конструкції, проаналізовано функції сепаратора щодо усування його перекосу, зменшення сил взаємодії з роликами і опорним кільцем, зменшення проковзування роликів. Це дозволило обґрунтувати зміни в конструкції сепаратора − збільшити кількість вікон, змінити форму бокових поверхонь перемичок і перерізу кілець сепаратора для підвищення технічного рівня РВБРТ в межах заданого габариту. The type of roller bearings used in axleboxes (supporting units) of rail transport systems (RBSRT) varies depending on the operating conditions specific to each country. In the United Kingdom, the United States, Japan, and Poland, railcars are equipped with wheelsets fitted with double-row tapered roller bearings. In Austria, Germany, and Ukraine, bearing units typically comprise two cylindrical roller bearings, while in Sweden, axlebox assemblies with two spherical roller bearings are standard. For structural and functional analysis, the most common series-produced cylindrical RBSRT units used in Ukrainian freight and passenger rolling stock−representing nearly 99% of the total−were selected as the baseline design. A structural decomposition of the primary bearing assemblies was performed in accordance with their functional roles. Based on the developed structural and functional model of the cylindrical roller bearing, functional interrelations between the bearing components were identified. The analysis focused particularly on the functions of the cage (separator), including prevention of skewing, reduction of interaction forces with the rollers and bearing ring, and minimization of roller slippage. These insights supported the rationale for design modifications of the cage−specifically, increasing the number of windows, altering the shape of the side surfaces of the bridges, and optimizing the cross-section of the cage rings−to enhance the technical performance of RBSRT while maintaining dimensional compatibility.
Structural and functional model of bearing assemblies in load-bearing units of rail transport systems
Keywords: технічний рівень; роликові вальниці букс; конструкція сепаратора; technical level; roller bearings axle box; separator design